(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article substantiates the urgency of the problem of humanization of education, determines the essence, content and peculiarities of communicatively directed education as a condition for the humanization of pedagogical activity, reveals the technology of its organization.